Hot pepper (Capsicum sp.) oil and its effects on growth performance and blood parameters in rainbow trout (Oncorhynchus mykiss) - Parrino, Vincenzo; Kesbiç, Osman Sabri; Acar, Ümit; Fazio, Francesco (Informa UK Limited, 2019)
The authors studied the effect of hot pepper (capsicum sp.) oil on the growth performance and blood parameters in rainbow trout fed. Hot pepper oil was added to rainbow trout feeds at the rates of HPO 0‰ (0 mg/kg) (control), HPO 1‰ (1 mg/kg), HPO 2‰ (2 mg/kg), HPO 4‰ (4 mg/kg) and HPO 6‰ (6 mg/kg), and the fish were fed with experimental feeds for 60 days. The group fed with HPO 4‰ showed the highest percentage growth rate and the lowest feed conversion rate. Our results showed the significant differences serum biochemical parameters, a decrease of serum liver enzymes, glucose, cholesterol and triglyceride levels and an increase of total protein and albumin levels compared with the control. The use of HPO 1‰ in rainbow trout showed a positively affects the growth performance, haematological and serum biochemical parameters.
Keywords: Aquaculture; Animal Feed; Enzymes; Cholesterol; Oncorhynchus mykiss; Oils, Volatile; Animals; Plant Oils; Capsicum; Capsicum, GC/MS, haematology, natural product, serum biochemistry; Triglycerides